Muzzling communication: Sedition law as a political tool to suppress dissent or a legal tool to manage ethnic relation? - Shuaib, Farid Sufian (2009)
Multi-ethnic and multi-religious make up of Malaysian society requires a deft hand in managing ethnic relation. Malaysia has histories of flares of ethnic relations such as the May 13 incident in 1969. One of the causes attributed to the incident is unruly speeches that incite inter ethnic hatred. Apart from social and economic policies and action-plans, laws regarding speech could also be used as a tool to prevent such incidents. Sedition law is one of the legislation uses to suppress speech that may incite violence between ethnic groups. The law has been used in number of incidents including political speeches that tend to cause ill feeling and hostility between ethnic groups. The courts have also decided in several cases to punish writers of seditious publication. However, there were also criticisms of abuse of sedition law in suppressing or inhibiting dissent against the government of the day. After 60 years of the Sedition Act 1948, it is timely to consider its usefulness and efficacy in managing ethnic relations. The paper seeks to analyse the use and abuse of sedition law by looking at legislation, judgement of the courts and reported incidents regarding sedition law. The paper also will consider whether there is a better legislative scheme to do the job of managing ethnic relation without abuse by politician.